Effect of the season on the free phytoprostane content in Cornicabra extra virgin olive oil from deficit‐irrigated olive trees. (3rd June 2015) - Collado‐González, Jacinta; Pérez‐López, David; Memmi, Houssem; Gijón, M Carmen; Medina, Sonia; Durand, Thierry; Guy, Alexandre; Galano, Jean‐Marie; Fernández, Diego José; Carro, Fernando; Ferreres, Federico; Torrecillas, Arturo; et al.
Abstract: BACKGROUND: The effect of regulated deficit irrigation (RDI) on the phytoprostane (PhytoP) content in extra virgin olive ( Olea europaea L., cv. Cornicabra) oil (EVOO) was studied. During the 2012 and 2013 seasons, T0 plants were irrigated at 100% ETc, while T1 and T2 plants were irrigated avoiding water deficit during phases I and III of fruit growth and saving water during the non‐critical phenological period of pit hardening (phase II), developing a more severe water deficit in T2 plants. In 2013, a fourth treatment (T3) was also performed, which was similar to T2 except that water saving was from the beginning of phase II to 15 days after the end of phase II. RESULTS: 9‐F1t ‐PhytoP, 9‐ epi ‐9‐F1t ‐PhytoP, 9‐ epi ‐9‐D1t ‐PhytoP, 9‐D1t ‐PhytoP, 16‐B1 ‐PhytoP and 9‐L1 ‐PhytoP were present in Cornicabra EVOO, and their contents increased in the EVOO from RDI plants. CONCLUSION: Deficit irrigation during pit hardening or for a further period of 2 weeks thereafter to increase irrigation water saving is clearly critical for EVOO composition because of the enhancement of free PhytoPs, which have potential beneficial effects on human health. The response of individual free PhytoPs to changes in plant water status was not as perceptible as expected, preventing their use as biomarkers of water stress. © 2015 Society of Chemical Industry